Vous êtes sur la page 1sur 208

(G n ) G τ n G n λ λ c (G) G τ n λ λ c (G) τ n 1 τ n

(G n ) G τ n G n τ n λ

λ c (G) G τ n

τ n 1

λ < λ c (G) λ < λ c (G)

Z d 0, n d

T d T n

d

1

 

 

1 < a < 2

a = 2

 

 

 

 

 

3.1.1.

 

 

 

 

 

G s s 1

 

 

RRG(R)

 

 

 

 

 

 

 

 

λ 1 λ

Z d T d d +1 70, 80 90

(G n ) G τ n G n λ λ c (G) G

τ n

G n λ

λ c (G)

τ n

1

τ n

G = (V, E) λ > 0

G (ξ t ) t 0 {0, 1} V

f(ξ) = (f(φ v ξ) f (ξ)) + λ (f(φ (v,w) ξ) f (ξ)),

vV

vw

v w {v, w} ∈ E

φ v ξ(w) =

ξ(w)

0

w

w = v,

= v,

φ (v,w) ξ(u) =

ξ(u)

1(max{ξ(x), ξ(y)} = 1)

w

w = v.

= v,

1(E) E

A V (ξ

(ξ

ξ t V ξ t = {v V : ξ t (v) = 1}

) A A = {v}

A

t

v

t

)

ξ t ξ t \ {v}

1

v

ξ t ξ t ∪ {v}

λ ξ t (v)

v

ξ

t

ξ t ,

ξ t (v) v t

1

λ

G

N v 1 v V N e λ e

(v, s) (w, t)

(v, s) (w, t),

s = t v = w s < t s = s 0 < s 1 <

s < s +1 = t v = v 0 , v 1 ,

i =

<

, v = w

1,

.

.

.

,

s i ∈ N (v i1 ,v i )

  N v i [s i , s i+1 ] = .

A V A

ξ

A

t

= {w V

: v V

(v, 0) (w, t)}.

Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ
Z t t t ξ A ∪ B t = ξ A t ∪ ξ

Z

t t t

ξ

AB

t

= ξ

A

t

ξ

B

t

A, B V.

λ λ 1 < λ 2 A t 0

ξ

A,(λ 1 )

t

ξ

A,(λ 2 )

t

,

) λ

λ 1 2

)

ξ

(ξ